African American learning-to-learn-to-live in response to diseducation: A phenomenological investigation - Margaret Shaw (Adult Education Research Conference, 1993)
The purpose of this research was to investigate the observed behaviors of successful African Americans and determine their patterns of learning. The "learning-to-learn-to-live" concept explained this pattern. —————————————-